Task force of the European federation of medical informatics journals: background, rationale and purpose - Mašić, Izet (Informatica Medica Slovenica, 2009)
The paper presents an analysis of how EFMI disseminates new knowledge and of the active medical informatics journals in EFMI member countries, which was carried out as an outcome of the EFMI Council meetings in London 2008, Sarajevo 2009 and Antalya 2009. The analysis identifies eight active major informatics journals and several other publications. Most are subscription-based and published at least quarterly. There is a possibility for the editors to meet regularly and form a community of practice with the aim of further improving their effectiveness in disseminating new knowledge and best practice in medical informatics. It is feasible to share expertise and it may be possible to harmonise several aspects of preparation and submission of manuscripts so that some of the identified barriers in publishing are reduced.
Keywords: Europe; Evropa; Kvaliteta, nadzor; Medical Informatics; Medicinska informatika; Periodicals; Periodika; Pisanje; Publishing; Quality Control; Writing; Založništvo